Comparative study of the production of rhamnolipid biosurfactants by B. thailandensis E264 and P. aeruginosa ATCC 9027 using foam fractionation. Issue 7 (July 2016) - Díaz De Rienzo, M.A.; Kamalanathan, I.D.; Martin, P.J.
Graphical abstract: Highlights: Rha-Rha-C14-C14 and Rha-C10-C10 were recovered in a continuous foam fractionation system. The yield of Rha-Rha-C14-C14 produced by B. thailandensis increased by a factor of 5. A competitive adsorption process was postulated to occur during the foam fractionation process. Abstract: Biosurfactants are surface-active agents that are produced by a variety of microorganisms including yeasts, filamentous fungi and bacteria. In this work, we report on the ability of Pseudomonas aeruginosa ATCC 9027 and Burkholderia thailandensis E264 to produce rhamnolipids via a 10-L bioreactor and their recovery through foam fractionation studies in a continuous stripping mode. The recovery of Rha-C10 -C10 (mono-rhamnolipids) produced by P. aeruginosa ATCC 9027 increased (from 6% to 96%), whilst the enrichment decreased (from 2.9 to 1.2) with the increasing airflow rate. These results are consistent with foam fractionation of a single surfactant system with stable foam. The recovery and enrichment of Rha-Rha-C14 -C14 (di-rhamnolipids) produced by B. thailandensis E264 (and an unknown molecule) in a single-component system were found to display different characteristics. Both recovery and enrichment were found to decrease with the airflow rate. It is postulated that a competitive adsorption process could occur between the smaller molecule identified by electrospray ionisation–mass spectrometry (ESI–MS) and Rha-Rha-C14 -C14 .